2017
DOI: 10.3390/rs9070720
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of GPM and TRMM Precipitation Products over Singapore

Abstract: The evaluation of satellite precipitation products (SPPs) at regional and local scales is essential in improving satellite-based algorithms and sensors, as well as in providing valuable guidance when choosing alternative precipitation data for the local community. The Tropical Rainfall Measuring Mission (TRMM) has made significant contributions to the development of various SPPs since its launch in 1997. The Global Precipitation Measurement (GPM) mission launched in 2014 and is expected to continue the success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
138
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(179 citation statements)
references
References 44 publications
18
138
1
3
Order By: Relevance
“…In contrast, a good correlation was found in China [28], Turkey [20], and Morocco [13]. A good correlation in these regions may be because more gauging stations were used in bias correction algorithm of TMPA products [5]. Selection of the limited number of reference ground-based gauging station in the bias correction algorithms of TMPA products could be one of the potential reasons behind poor correlations of TMPA products with reference gauges data in the northern Pakistan.…”
Section: Accuracy Of Tmpa Products At Different Precipitation Intensimentioning
confidence: 63%
See 1 more Smart Citation
“…In contrast, a good correlation was found in China [28], Turkey [20], and Morocco [13]. A good correlation in these regions may be because more gauging stations were used in bias correction algorithm of TMPA products [5]. Selection of the limited number of reference ground-based gauging station in the bias correction algorithms of TMPA products could be one of the potential reasons behind poor correlations of TMPA products with reference gauges data in the northern Pakistan.…”
Section: Accuracy Of Tmpa Products At Different Precipitation Intensimentioning
confidence: 63%
“…The upgraded algorithm used in 3B42V7 combines the estimates from the MW Humidity Sounder (MWHS), TRMM Precipitation Radar (TPR), SSMI, GPCC, and National Climatic Data Centre (NCDC). After the success of TRMM project, NASA and JAXA launched a successor to TMPA products in early 2014, known as GPM product (not included in this study), by combining the algorithm of upgraded TMPA product with Climate Prediction Centre Morphing technique (CMORPH) and Precipitation Estimation from the Remotely Sensed Information Using Artificial Network (PERSIANN) [5]. Therefore, comprehensive assessments and comparisons of the performance of the upgraded TMPA algorithm relative to its predecessor and real time versions in different regions, precipitation patterns and topographic conditions would be valuable for algorithm developers, particularly for GPM, as well as satellite-based precipitation data users.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the relative magnitude of TRMM rain accumulation compared to rain gauge accumulation is smaller for higher rainfall intensity events. Tan and Zheng [45] evaluated the detection capability of two TRMM products (3B42 and 3B42RT) in Singapore, and found that satellite products do not capture Table 1). …”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the performance of TRMM 3B42 v7 and GPM IMERG v5 precipitation products and ensure proper error analysis on a grid basis at multiple scales over the basin, the specified location or pixel for each rain gauge was checked, and then, the spatial-temporal coincident satellite pixel with corresponding gauges was evaluated [15,20]. Only the satellite grids that covered at least one rain gauge were evaluated, and the other grids with no rain gauges were excluded from the evaluation.…”
Section: Methodologiesmentioning
confidence: 99%